An atypical case of eosinophil-Rich Sweet's syndrome - Yosra Soua; Mohamed Ben Rjeb; Adnène Moussa (Our Dermatology Online, 2021)
Sweet's syndrome is an inflammatory disease that occurs mainly in young adults. Its clinical and histological aspects are usually characteristic. Its diagnostic criteria were proposed by von den Driesch. Two major and at least two minor criteria are required to establish the diagnosis. Sweet's syndrome is classically associated with neutrophilic infiltrate. A few cases of Sweet's syndrome with dense eosinophil infiltrate have been described. Here, we report a new case of eosinophil-rich Sweet's syndrome in a young woman without underlying pathology.